Living Racism : Through the Barrel of the Book. - Brooms, Derrick R. (Lexington Books, 2017)
This book explores how racism lives and how racism is lived. Earlier chapters provide the theoretical foundation for the later chapters on contemporary racial issues. Collectively they show change, continuity, and diversity of racial thinking and outcomes.